Internal factors that stimulate the internationalization of companies in Peru’s jewellery sector - Jara Mateo, Jhanira Geraldini (2020)
The purpose of this research is to make known the internal factors that stimulate the internationalization of companies in the jewelery sector. We consider the qualitative approach at the descriptive level through semi-structured interviews with twelve major exporting companies in the jewelery sector in Peru. The results of the investigation show that the most relevant internal factors for the internationalization of jewelry companies is the international experience based on the understanding of markets, foreign clients, competition, knowledge of the documents and certificates necessary for an export, international commercial relations and risks in the negotiations; Another relevant internal factor is the personaliza- tion of the product with characteristics of innovation that generates better export results and, therefore, have a competitive position, since in the international market customers consider that companies have a product with added value, innova- tive and competitive. Moderately relevant factors are transaction costs, firm size, and the tacit nature of know-how; while opportunistic behaviuor is of little relevance. These findings will serve to understand opportunities and limitations that companies must be aware of to undertake new internationalization projects in the jewelery sector.